(untitled) (Research, Society and Development, 2019)
The Academic Master’s Program in Teaching PPGEn was created by means of a Technical Scientific Cooperation Agreement between the Federal Institute of Education, Science and Technology of Mato Grosso - IFMT and University of Cuiabá-UNIC, through Resolution CONSUP IFMT nº 100 on November 26 The course aims to develop an interdisciplinary work that integrates the different areas of knowledge. This article results from the practice of the researcher as a teacher of the Program and aims to understand about the teaching of the training offered by the program to its students in the interdisciplinary perspective. It is a qualitative research that used as a methodology the Training Narratives, which works punctually with personal and collective paths of subjects involved in educational environments. As a result, it was realized that the practice developed in the Master in Teaching takes place through the perception that the teacher is par excellence researcher, possibility that the interdisciplinary practice developed through collective actions has generated. This has been done as a reflection of educational pedagogical action, to enable the teacher to examine it with the look of who is mediator of the process of knowledge construction.